The impact of racism on emergency health care workers. (6th August 2021) - Kaltiso, Sheri‐Ann O.; Seitz, Roslyn M.; Zdradzinski, Michael J.; Moran, Timothy P.; Heron, Sheryl; Robertson, Jennifer; Lall, Michelle D.
Abstract: Introduction: Discrimination based on race is a known source of stress in individuals and is a contributor to poor health outcomes in patients. However, less is known about how the experiences of racism impact the stress levels of emergency health care workers (EHCWs). Objectives: The goal of this study was to assess the impact that racism has on the stress of EHCWs. Methods: An anonymous electronic cross‐sectional survey of EHCWs including attending physicians, resident physicians, advanced practice providers, nurses, and staff at three large metropolitan hospitals was administered in the summer of 2020. The survey evaluated the stress related to systemic racism and the COVID‐19 pandemic in addition to the wellness measures utilized to cope with these stressors. The focus of this article is the impact of systemic racism on EHCWs. Results: Of the 576 eligible participants, the total number of respondents utilized for analysis was 260. Overall, 64% of participants were very concerned about the state of racism in the United States, and 30% reported moderate–high or high stress resulting from racism. When stratified by race, 46% of Black participants reported moderate–high or high stress resulting from racism, compared to 31% of other participants of color and 23% of White participants (p = 0.002). Conclusion: Systemic racism is a significant concern and source of stress for EHCWs. Additional research about systemic racism, its impact on medical providers, and more importantly, active strategies to reduce and ultimately eliminate it in health care is needed.